L'éducation relative à l'environnement sous l'ère néolibérale : ombres et lumières à l'heure du changement climatique - Edgar J. González Gaudiano
An analysis of the trajectory of environmental education since 1987 reveals the institutional and pedagogical consequences of promoting education for sustainable development. This is an integral part of the overall neoliberal strategy aimed at establishing social conditions more favorable to the current phase of capitalism where economic ends prevail over cultural norms. The educational dimension of this issue is examined here, paying particular attention to the case of Mexico. It is important that education seizes the grip of neoliberalism and in particular the problem of consumption and its illusory promise of rise and social distinction, as well as its socio-environmental consequences on the oceans, the atmosphere, the biodiversity, soils, health, inequalities, migration, etc. Finally, we will focus more specifically on the problem of climate change, highlighting the politico-educational issues that such a global crisis raises.